Cull cow management and its effect on performance and carcass characteristics - Grassi, Celso; Müller, Lauro (Pesquisa Agropecuaria Brasileira, 1991)
Forty-four Charolais and 28 Angus cows with age ranging from seven to eleven years were randomly distributed within each breed into four treatments: T1 - open cows; T2 - pregnant cows; T3 - spayed cows and T4 - cows with IUD (Intra-Uterine Device). The experimental period lasted 185 days, beginning in November 11, 1978 and ending in May 14, 1979. Then, all the cows were slaughtered. During the experiment all the cows remained in native pasture. The average daily gain for T1, T2, T3 and T4 was: 0.307, 0.428, 0.270 and 0.276, respectively. Pregnant cows presented a higher daily gain than the other three groups (P < 0.05). No significant difference was found in all the carcass parameters studied, athough pregnant cows displayed a thicker cover of external fat. The evaluation of tenderness even by Taste Panel or through the Warner-Bratzler shear device as well flavor, juiciness and losses during thawing and cooking process, showed small and nonsignificant differences. The results of this experiment show that the finishing period should be conducted with cows that were left open.